MILITARY ACADEMY CADET EDUCATIONAL MODEL IN FIELD LEADERSHIP CHARACTER BUILDING - Wijanarko, Heri; Sudijono, Sudijono; Sugiharto, D.Y.P. (Universitas Negeri Semarang, 2017)
Previous researchers have found that leadership directly influences character building. Teaching factors, training, and educational counseling become mediation in character building and organizational culture influence. This research aims at evaluating and developing Military Academy Cadet educational model in field leadership character building by proposing seventeen hypotheses to analyze and describe direct and indirect influence of educational leadership independence variable and organizational culture through learning intervening variable, training, and educational counseling toward field leadership independence variable. This research method used qualitative approach. The sample was taken by random sampling technique with 249 cadets as the population. Based on Slovin calculation, with Î± = 0,05the sample was 153 cadets. Data collection used behavior scale instrument with proven validity and reliability. Data analysis was performed by using IBM SPSS 22and SmartPLS 2.0 software. Estimation result on theoretical model showed that model was not fit. Theoretical model development in alternative model C showed that the fit model fulfilled the goodness of fit with convergent validity>0,5, discriminant validity>0,7, average variance extracted (AVE) > 0,5, composite reability>0,7, cronbahs Alpha>0,6, communality > 0,5,dan R-square. The result of hypothesis test in general has T-statistics score >1,96. This finding model evaluates educational counseling theory by the empiric fact that educational counseling mediates educational leadership and organizational culture toward learning process. Thus, it recommends to develop educational counseling to increase its contribution toward learning and training in building field leadership character of Military Academy Cadet.